Facile nucleophilic substitution approach for the spectrofluorimetric assay of natamycin based on diarylpyrrolone formation, evaluation of method greenness - Sayed M. Derayea; Fatma F. Mohammed (BMC Chemistry)
Abstract An ecofriendly, effective, and selective spectrofluorimetric approach for natamycin analysis was developed using fluorescamine as a fluorogenic probe. Natamycin is the only topical ocular antifungal medication that is presently on the market for treating keratitis, conjunctivitis, and blepharitis caused by yeast and other fungi. Owing to its primary aliphatic amino group, natamycin can easily interact with fluorescamine resulting in the formation of the highly fluorescent diaryl pyrrolone derivative. The derivatization reaction was completed within very short time at room temperature in borate buffer solution (pH 7.6). The fluorescence intensity of the reaction product was monitored at 465 nm after exciting at 390 nm. The linearity range of the spectrofluorimetric method was 0.25–4.0 µg/mL of natamycin with limit of detection (LOD) of 0.082 µg/mL. The method was applied for the determination of the cited drug in pharmaceutical eye drops and artificial aqueous humor with high percentage recoveries and low relative standard deviations. In addition, the involved analytical procedure was green based on the results of the ecology scale scores.